2023
DOI: 10.1111/cns.14412
|View full text |Cite
|
Sign up to set email alerts
|

Human umbilical cord derived mesenchymal stem cells overexpressing HO‐1 attenuate neural injury and enhance functional recovery by inhibiting inflammation in stroke mice

Yu Yang,
Qianqian Liu,
Song Deng
et al.

Abstract: AimsThe current evidence demonstrates that mesenchymal stem cells (MSCs) hold therapeutic potential for ischemic stroke. However, it remains unclear how changes in the secretion of MSC cytokines following the overexpression of heme oxygenase‐1 (HO‐1) impact excessive inflammatory activation in a mouse ischemic stroke model. This study investigated this aspect and provided further insights.MethodsThe middle cerebral artery occlusion (MCAO) mouse model was established, and subsequent injections of MSC, MSCHO‐1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 43 publications
(101 reference statements)
0
1
0
Order By: Relevance
“…This modified approach to MSC provides valuable insights into the development of treatments for neuroinflammation-related diseases. At the same time, although many previous studies have confirmed that MSC injected through the tail vein can enter brain tissue via the blood-brain barrier [ 19 , 45 ], we can still continue relevant research work in future studies. In order to better understand the mechanism of action of MSC, we plan to use Dil labeling technology to label MSC in subsequent studies and then inject them into mice via the tail vein.…”
Section: Discussionmentioning
confidence: 96%
“…This modified approach to MSC provides valuable insights into the development of treatments for neuroinflammation-related diseases. At the same time, although many previous studies have confirmed that MSC injected through the tail vein can enter brain tissue via the blood-brain barrier [ 19 , 45 ], we can still continue relevant research work in future studies. In order to better understand the mechanism of action of MSC, we plan to use Dil labeling technology to label MSC in subsequent studies and then inject them into mice via the tail vein.…”
Section: Discussionmentioning
confidence: 96%